The Potential of ZIS Fund As an Instrument in Islamic Economy: Its Theory and Management Implementation - Budi Budiman (Jurnal Iqtisad, 2003)
Zakah, infaq and shadaqah (ZIS) are proven to have significant roles in the development of Islam and Moslems in Indonesia. This fact can be seen among others from the number of mosques in all scale, schools and madrasah, Islamic boarding schools, orphanages, uni-versities, hospitals, and public health clinics, as well as public meeting rooms which are built with funding from zakah, infaq, shadaqah and waqf, beside from governmental aids.However, the more important fact is that zakah needs to be positioned as a source of public revenue with which impecunious people’s esteem can be promoted. It is not easy, of course. Many things should be done in ZIS fund management, from arranging legislations to preparing human resources that are not only comprehending zakah management but also having trustworthiness as organizers of ZIS fund.Many factors causing contradiction between the potential of zakah and the number of impecunious people in Indonesia, among others, the inability of zakah management bodies (i.e. BAZ or LAZ according to the Act No. 38 Year 1999 concerning Zakah Management) to attain the expected level of service quality. Though in the last ten years Indonesian Mos-lems begin to realize the obligation to pay zakah, but the condition of the poor and the needy is still practically unchanging.